Integrative bulk and single-cell transcriptomics link EZH2 to immunosuppressive programs and tumor–Treg crosstalk in castration-resistant prostate cancer - Xiong, Xing; Xie, Jianhu; Dai, Ping; Cheng, Chao; Liu, Jiani; Huang, Guixiao (Frontiers in Immunology, 2026)
BackgroundEnhancer of zeste homolog 2 (EZH2) is frequently upregulated in prostate cancer (PCa) and further increased in castration-resistant prostate cancer (CRPC), a lethal state characterized by profound immune dysfunction. However, EZH2-associated immune programs in bulk cohorts and their corresponding cell-type–specific features in single-cell RNA sequencing (scRNA-seq) data have not been systematically delineated in advanced PCa.MethodsWe integrated bulk RNA-seq and scRNA-seq to map EZH2-associated transcriptional and immune features in PCa. In bulk cohorts (TCGA-PRAD and an independent metastatic CRPC cohort), we quantified EZH2 expression, clinical outcomes, and immune-signature enrichment. Immune-modulated differentially expressed genes (IMDEGs) were defined by intersecting EZH2-associated differential expression with correlations to Treg/TAM-related signature scores, and were used for NMF-based immune subtyping and penalized Cox modeling with validation. In scRNA-seq cohorts (GSE264573 and an independent CRPC cohort), malignant epithelial cells were inferred by copy-number alteration profiles, EZH2^high versus EZH2^low malignant programs were characterized, T-cell subsets were quantified, and tumor–Treg communication was inferred using CellPhoneDB as hypothesis-generating predictions. For perturbation, the EZH2 inhibitor tazemetostat was evaluated in the CRPC-relevant C42 cell line with H3K27me3 readouts and transcriptomic profiling, with key changes validated by RT–qPCR.ResultsAcross bulk cohorts, higher EZH2 expression was associated with adverse clinical outcomes and increased enrichment of immunosuppressive signatures, including Treg- and TAM-related programs. IMDEG-based NMF subtyping identified patient groups with distinct immune states, and an IMDEG-derived risk score stratified prognosis. Single-cell profiling revealed elevated EZH2 in CRPC malignant cells and Tregs; EZH2^high malignant cells exhibited a proliferative transcriptional state accompanied by reduced expression of immune-related programs. Predicted tumor–Treg interaction patterns were stronger in CRPC and positively associated with EZH2 expression. In C42 cells, tazemetostat reduced H3K27me3 and induced coordinated transcriptional changes, including upregulation of immune- and inflammation-associated genes such as TIMP3, PLCG2, and SOCS3, validated by RT–qPCR.ConclusionThis multi-layer integrative analysis suggests that EZH2 is associated with proliferative malignant states and immunosuppressive microenvironment features in advanced PCa, including Treg-linked crosstalk. Transcriptomic profiling following EZH2 inhibition supports modulation of these programs by EZH2-targeted perturbation, while functional and causal mechanisms warrant further investigation.